0
$\begingroup$

Assume N is a normal subgroup of G. Assume E is a subgroup of G/N. Thus E is a collection of right cosets of N in G. Let K be the set consisting of all the elements of G in the right cosets in E.

A)Prove that K is a subgroup of G that contains N. What is |K|?

B)Prove that K is normal in G if and only if E is normal in G/N.

I ran into this question and has a bit problem understanding "Let K be the set consisting of all the elements of G in the right cosets in E." What does it mean "cosets" there? Is it the cosets of K, which are in E?

$\endgroup$
  • $\begingroup$ They are saying that $K$ is the union of the cosets of $N$ which make up $E$. Another way of looking at it, if $\phi:G\to G/N$ where $\phi:g\mapsto Ng$, then $K=\phi^{-1}(E)$. $\endgroup$ – Tim Raczkowski Mar 19 '15 at 3:54
1
$\begingroup$

Let's look at an example:

Suppose $G = \Bbb Z_{30}$ and $N = \langle 6\rangle = \{0,6,12,18,24\}$.

Then $G/N = \{N, N+1, N+2, N+3, N+4,N+5\}$

Let's take $E = \{N,N+2,N+4\} = \langle N+2\rangle$

Now $N+2 = \{2,8,14,20,26\}$ and $N+4 = \{4,10,16,22,28\}$, so:

$K = N \cup (N+2) \cup (N+4) = \{0,2,4,6,8,10,12,14,16,18,20,22,24,26,28\} = \langle 2\rangle$.

How does $E$ compare with $K/N$?

Now here, it is clear to see that $K$ is, in fact, a subgroup of $G$. But one example does not prove the general case.


So proving (A) involves 2 things: proving $K$ is a subgroup, and that $N \subseteq K$. Let's do the second part, first.

So pick any old element $n \in N$. Then $n$ is in the coset $N$, which is in EVERY subgroup of $G/N$, since $N$ is the identity of $G/N$. So $N \in E$, and thus $n$ is in some coset in $E$, so $n$ is in $K$. Thus $n \in N \implies n \in K$, so $N \subseteq K$.

Now let's suppose that $x,y \in K$. This means that $x \in Ng$ for some coset $Ng \in E$, and similarly $y \in Nh$, for some coset $Nh \in E$.

Since $E$ is a subgroup of $G/N$, it is closed under multiplication, thus $(Ng)(Nh) = Ngh \in E$.

Since $x \in Ng, x = ng$ and since $y \in Nh, y = n'h$ for some $n,n' \in N$. Since $N$ is normal, we have $Ng = gN$, so $ng = gn_1$ for some $n_1 \in N$. This means:

$xy = ngn'h = gn_1n'h$. Since $n_1n' \in N,\ gn_1n' \in gN = Ng$, so $gn_1n' = n_2g$ for some $n_2 \in N$.

Hence $xy = gn_1n'h = n_2gh \in Ngh$, and $Ngh \in E$, so $xy \in K$. This shows $K$ is closed under multiplication.

Finally, let $x \in K$. Then $x \in Ng$ for some $Ng \in E$. Since $E$ is a subgroup of $G/N$, we have $(Ng)^{-1} = Ng^{-1} \in E$. Now $x = ng$, so $x^{-1} = g^{-1}n^{-1} \in g^{-1}N$. Now $N$ is normal, hence $g^{-1}N = Ng^{-1}$, and we have shown if $x \in K$, that:

$x^{-1} \in Ng^{-1} \in E$, so $x^{-1} \in K$, and $K$ possesses all inverses. Thus $K$ is a subgroup of $G$ containing $N$.


If you know that $\phi:G \to G/N$ is a homomorphism, all this becomes MUCH easier.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.